2011
DOI: 10.1080/1064119x.2010.514237
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Engineering Characteristics of Composite Geomaterial for Recycling Dredged Soil and Bottom Ash

Abstract: This article describes an experimental evaluation of engineering characteristics of composite geomaterial (CGM). Using several series of unconfined compression tests, flow tests, direct shear tests, and elastic wave tests. The experimental results indicated that flow value of CGM depended greatly on water content of the soil mixture, and unconfined compressive strength as well as stress-strain behavior of CGM were strongly influenced by the content of each component in the mixture. Unconfined compressive stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…It was also able to provide significant strength and stability to soil. As for WGM, 50-100 % of BA and POC resulted with higher strength gain and stiffness for a longer curing time [23], [28]. According to [29], the strength and stiffness of soil admixed with BA were influenced by the interparticle bonding at which the angularity structure of WGM had increased surface-to-surface contact and then further strengthen with cementation caused by pozzolan reaction.…”
Section: Sample Preparation and Test Methodsmentioning
confidence: 99%
“…It was also able to provide significant strength and stability to soil. As for WGM, 50-100 % of BA and POC resulted with higher strength gain and stiffness for a longer curing time [23], [28]. According to [29], the strength and stiffness of soil admixed with BA were influenced by the interparticle bonding at which the angularity structure of WGM had increased surface-to-surface contact and then further strengthen with cementation caused by pozzolan reaction.…”
Section: Sample Preparation and Test Methodsmentioning
confidence: 99%
“…Many studies have proven that cement content at minimum of 10% had improved the engineering properties of DMS [20], [21]. Moreover, previous researchers have reported that 50-100% of BA and POC have resulted with significant gain of strength and stiffness which was influenced by the inter-particle bonding and pozzolanic reaction of these granular materials [19], [22], [23]. Hence, 50 and 150% of BA and POC by dry weight of soil were also used in this study.…”
Section: Summaries Of Physical and Chemicalmentioning
confidence: 99%
“…Because the strength of the cement-admixed clay does not linearly increase with the cement content [18], the utilization of BA in partially replacing cement or adding up could substantially reduce the use of cement, particularly when the high-strength cemented clay is required. A previous study [19] revealed two different mechanisms involving the strength increase of BA-added composite geomaterials: particle bonding and fabric change. The first one is attributed to the pozzolanic reaction, and the latter one deals with the packing effect.…”
Section: Introductionmentioning
confidence: 98%